Performance evaluation of passive control device for efficient steel space structures - Lakshmikandhan, K.N.; Sivakumar, P.; Ravichandran, R.; Senthil, R. (Journal of Structural Engineering, 2024)
The steel space frame structures are popular in covering the large areas with or without intermittent supports. Steel space structures are more advantageous in lower weight to usage ratio. The space structures are frequently reported for their catastrophic nature of failure. The catastrophic failure is generally initiated from one or few critical compression chord member nearer to truss support. The initial stresses developed in the space structure due to the uncertainties causes the over stressing of members. The space structures have about 25% of indeterminate members which redistribute these initial stresses and generate the secondary effects. All these finally affects the critical compression member behaviour and leads to catastrophic failure. This catastrophic nature of failure should necessarily be reduced by altering member force of members at specific location by using new technological advents. In the present study, numerous papers were reviewed and presented a better review on the active and passive control mechanisms, which are investigated to improve the performance of space structure. The present study aimed to make use of this member imperfection to improve the space truss capacity. A novel double sleeve system is developed to alter the member force of critical compression member using lack of fit concept. This performs as a passive force control device by manually adjusted member post-stress developing system. The passive control device changes the member length and introduces the prestressing force. Three numbers of three-bar space truss system and one four-bar space truss structure are investigated experimentally and verified analytically. The study showed evidence for altering about 20 to 25 percent of compression force in the critical compression member. Also, the experimental study showed its efficiency in shifting the brittle compression member failure to ductile tension member failure.